2023
DOI: 10.1051/0004-6361/202346695
|View full text |Cite
|
Sign up to set email alerts
|

An overdensity of Lyman break galaxies around the hot dust-obscured galaxy WISE J224607.56−052634.9

Abstract: We report the identification of Lyman Break Galaxy (LBG) candidates around the most luminous Hot Dust-Obscured Galaxy (Hot DOG) known, WISE J224607.56−052634.9 (W2246−0526) at z = 4.601, using deep r-, i-, and z-band imaging from the Gemini Multi-Object Spectrograph South (GMOS-S). We use the surface density of LBGs to probe the Mpc-scale environment of W2246−0526 to characterize its richness and evolutionary state. We identify LBG candidates in the vicinity of W2246−0526 using the selection criteria developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(126 reference statements)
1
2
0
Order By: Relevance
“…The X-ray observations of Hot DOGs consistently find high column densities that are close to Compton thick (Stern et al 2014;Piconcelli et al 2015;Assef et al 2016;Ricci et al 2017;Vito et al 2018;Zappacosta et al 2018;Assef et al 2020). The environments where Hot DOGs reside were found to be significantly overdense (Jones et al 2015;Silva et al 2015;Jones et al 2017;Penney et al 2019;Ginolfi et al 2022;Luo et al 2022;Zewdie et al 2023). All results are generally consistent with the merger-driven coevolution scenario.…”
Section: Introductionsupporting
confidence: 66%
“…The X-ray observations of Hot DOGs consistently find high column densities that are close to Compton thick (Stern et al 2014;Piconcelli et al 2015;Assef et al 2016;Ricci et al 2017;Vito et al 2018;Zappacosta et al 2018;Assef et al 2020). The environments where Hot DOGs reside were found to be significantly overdense (Jones et al 2015;Silva et al 2015;Jones et al 2017;Penney et al 2019;Ginolfi et al 2022;Luo et al 2022;Zewdie et al 2023). All results are generally consistent with the merger-driven coevolution scenario.…”
Section: Introductionsupporting
confidence: 66%
“…Studies have increasingly shown that Hot DOGs reside in overdense environments, characterized by a high frequency of galactic mergers (Jones et al 2014;Jones 2017;Assef et al 2015;Díaz-Santos et al 2018;Penney et al 2019;Luo et al 2022;Ginolfi et al 2022;Zewdie et al 2023). Despite hosting powerful AGNs, the host galaxies of high-z Hot DOGs are gasrich (Penney et al 2020;Díaz-Santos et al 2021;L.…”
Section: Optical Emissionmentioning
confidence: 99%
“…By imaging the [C II] emission in extremely luminous DOGs (L bol > 10 14 e ) ALMA, however, Díaz-Santos et al (2021) proposed instead that this short-lived phase may be triggered by a minor merger and might occur recurrently throughout the history of the galaxy. This is particularly plausible if Hot DOGs become the brightest galaxies in clusters once the overdensities they live in (Jones et al 2014;Jones 2017;Assef et al 2015;Luo et al 2022;Ginolfi et al 2022;Zewdie et al 2023) become virialized.…”
Section: Optical Emissionmentioning
confidence: 99%